2019
DOI: 10.1007/s10853-019-03551-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a tetrazine–quaterthiophene copolymer and its optical, structural and photovoltaic properties

Abstract: Herein, we report the synthesis of a novel, tetrazine-based conjugated polymer. Tetrazines have the benefit of being strong electron acceptors, while little steric hindrance is imposed on the flanking thiophene rings. Conversion of a suitably substituted nitrile precursor led to 3,6-bis(5-bromo-4-(2-octyldodecyl)thiophen-2-yl)-1,2,4,5-tetrazine (2OD-TTz). Palladium-catalyzed copolymerization of 2OD-TTz with a bithiophene monomer yielded an alternating tetrazine–quaterthiophene copolymer (PTz4T-2OD). The polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The corresponding mass loss of 3% can be assigned to the loss of one equivalent of nitrogen per repeating unit. 24 Li et al reported a 90% yield for this reaction which was in line with our observation. 12 Compared to tetrazines, pyrrolopyridazine (PPD) monomers have an increased electron-deficient character and are furthermore more thermally stable than the respective tetrazines.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…The corresponding mass loss of 3% can be assigned to the loss of one equivalent of nitrogen per repeating unit. 24 Li et al reported a 90% yield for this reaction which was in line with our observation. 12 Compared to tetrazines, pyrrolopyridazine (PPD) monomers have an increased electron-deficient character and are furthermore more thermally stable than the respective tetrazines.…”
Section: Introductionsupporting
confidence: 92%
“…This allows for tuning the polymer properties, but at the cost of more synthetic effort for obtaining the required nitriles. Recently, we followed the approach of incorporating large branched alkyl side chains into the tetrazine based monomer and attempted to combine the necessity of the large alkyl chains with the benefit of an improved phase separation and domain purity in the absorber layer as exemplified by Liu et al 23,24 Combination of this tetrazinequaterthiophene copolymer with the NFA ITIC-F (3,9-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23]. R f (CH 2 Cl 2 / MeOH 20/1) = 0.21; 1 H NMR (300 MHz, CDCl 3 , 25 °C): δ = 8.77-8.69 (m, 2H, py 3,6 ), 8.67 (d, 1H, 3 J HH = 5.0 Hz, py 6 ), 8.60 (s, 1H, pz 5 ), 8.30 (d, 1H, 3 J HH = 8.0 Hz, py 3 ), 7.97…”
Section: -[36-di(pyridin-2-yl)pyridazin-4-yl]mentioning
confidence: 99%
“…Since the first report of the synthesis of pyridazines from tetrazines and alkenes, allenes, or alkynes by Carboni and Lindsey in 1959 [1], this reaction received ever increasing attention first because of its synthetic potential in heterocyclic chemistry [2] and later in chemical biology applications because particular tetrazine/olefin combinations provide exceptionally fast and selective ligation reactions at very low concentrations [3]. Additionally, applications in material chemistry evolved [4][5][6]. The mechanistic understanding of the inverse-electron demand Diels-Alder cycloaddition (iEDDA) reactions, the broader term for the reaction of a tetrazine with an olefin giving a pyridazine derivative, is well developed and nicely summarized in a recent review article [7].…”
Section: Introductionmentioning
confidence: 99%